Deciphering the role of plant plasma membrane lipids in response to invasion patterns: how could biology and biophysics help?. (30th November 2021) - Cordelier, Sylvain; Crouzet, Jérôme; Gilliard, Guillaume; Dorey, Stéphan; Deleu, Magali; Dhondt-Cordelier, Sandrine
Abstract: Plants have to constantly face pathogen attacks. To cope with diseases, they have to detect the invading pathogen as early as possible via the sensing of conserved motifs called invasion patterns. The first step of perception occurs at the plasma membrane. While many invasion patterns are perceived by specific proteinaceous immune receptors, several studies have highlighted the influence of the lipid composition and dynamics of the plasma membrane in the sensing of invasion patterns. In this review, we summarize current knowledge on how some microbial invasion patterns could interact with the lipids of the plasma membrane, leading to a plant immune response. Depending on the invasion pattern, different mechanisms are involved. This review outlines the potential of combining biological with biophysical approaches to decipher how plasma membrane lipids are involved in the perception of microbial invasion patterns. Abstract : Combined biological and biophysical approaches emphasize novel insights into the key role of plasma membrane lipids in the sensing of microbial invasion patterns during plant innate immunity.